PH-triggered Release of Boron and Thiamethoxam from Boric Acid Crosslinked Carboxymethyl Cellulose Hydrogel Based Formulations. Issue 1 (2nd January 2019) - Sarkar, Dhruba Jyoti; Singh, Anupama
ABSTRACT: Boric acid crosslinked carboxymethyl cellulose hydrogels were synthesized to develop pH-triggered release formulations (pH-TRFs) of boron and thiamethoxam. The developed hydrogels showed pH sensitive water absorption capacity (16.75 to 110.80 g/g xerogel). Entrapment of thiamethoxam was done through an ex-situ loading technique. The boron and thiamethoxam release was studied in pH buffer solutions (4.0, 7.0 and 9.2). Release kinetics analysis using mathematical models showed fast release in high pH solution as compared to acidic pH. These pH-TRFs may find usefulness in selective release of nutrients and pesticides in plant rhizospheric zone of problem soils viz. acidic soils and alkaline soils. GRAPHICAL ABSTRACT: